Comparative study of aflatoxin B1adsorption by Thai bentonite and commercial toxin binders at different temperatures in vitro - S. Wongtangtintan (2018)
© 2016, Fundacion CIPAV. All Rights Reserved. Thai bentonite (TB) and two commercial toxin binders including commercial bentonite (CB) and activated carbon (AC) were investigated for their adsorption capacities of aflatoxin B1(AFB1) at different temperatures in vitro. Each sample of 5 mg/l AFB1solution was shaken at 25̊, 37̊and 45̊C for 24 hours, and the supernatants of centrifuged samples were analyzed for concentrations of AFB1using a UV spectrophotometer at a wavelength of 362 nm. The results indicated that TB is capable of sequestering AFB1from aqueous solutions and had significantly greater adsorption capacities than CB and AC (p<0.05). The adsorption capacities were then calculated and applied to isotherm equations. The linearized Langmuir and linearized Freundlich adsorption isotherm equations indicated that TB was the best toxin binder for adsorbing AFB1as demonstrated by its significantly higher estimated maximum binding capacity (p<0.05), the distribution coefficient and the heterogeneity factor. The mean adsorptions of AFB1on all binders were highest at 25̊C, whereas adsorbed significantly decreased when temperatures were increased from 25̊C to 45̊C (p<0.05). Furthermore, the results revealed that the Freundlich model presented a better fitted to the experimental data than the Langmuir model. This implied that the adsorption behavior of AFB1on these toxin binders represented multilayer/multiple site adsorption on the binders’ surfaces. The results support the conclusion that TB adsorbs AFB1in vitro more efficiently than other commercial toxin binders, especially at 25̊C.